2020
DOI: 10.1002/jcaf.22479
|View full text |Cite
|
Sign up to set email alerts
|

Debt maturity structure and cost stickiness

Abstract: This paper investigates the association between debt maturity structure and cost stickiness. One view in the cost stickiness literature suggests that managers deliberately continue to expand resources for their own private benefit, despite a decrease in the activity level. We examine whether short‐maturity debt constrains such opportunistic cost stickiness. We find evidence supporting this hypothesis. We further document that availability of free cash flows, earnings management incentive, and the structure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…Debt load can be considered to be a crucial aspect of businesses. Habib and Costa (2021) argued that external stakeholders, especially lenders, can keep an eye on management to prohibit them from conserving resources against the interests of the company and preventing agency issues when sales decrease, and short-term debts can lessen the level of cost stickiness. This is consistent with Calleja et al (2006) who found that companies with higher debt levels showed symmetric cost behavior.…”
Section: Cost Stickiness and Debt Intensitymentioning
confidence: 99%
“…Debt load can be considered to be a crucial aspect of businesses. Habib and Costa (2021) argued that external stakeholders, especially lenders, can keep an eye on management to prohibit them from conserving resources against the interests of the company and preventing agency issues when sales decrease, and short-term debts can lessen the level of cost stickiness. This is consistent with Calleja et al (2006) who found that companies with higher debt levels showed symmetric cost behavior.…”
Section: Cost Stickiness and Debt Intensitymentioning
confidence: 99%
“…Management optimism is another important cause of expense stickiness (Lee et al , 2020). If management insists that performance will improve in the future, that is, management optimism, the cost will not be significantly adjusted due to income decreases (Habib and Costa, 2021). Conversely, if managers expect adverse future conditions, that is, management pessimism, they will reduce investment to maintain the status quo.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…‫منها‬ ‫يذكر‬ ‫بشقيه‬ ‫المال‬ ‫رأس‬ ‫وتكلفة‬ ‫السلوك،‬ ‫متباينة‬ ‫التكلفة‬ ‫بين‬ ‫المحتملة‬ ‫العالقة‬ ‫الدراسات‬ ‫من‬ ‫مجموعة‬ ‫تناولت‬ (Habib & Costa, 2021. Zhong et al, 2020.…”
Section: ‫المفتاحية‬ ‫الكلمات‬unclassified